An analysis on tensile and flexural loading response for unidirectional CFRP laminate with cutout/hole: Geometrical design effect on the material strength. Issue 46 (22nd September 2022) - Gupta, Savita; Pal, Snehanshu; Ray, Bankim Chandra
Abstract: A comparative analysis has been done on CFRP laminate to understand the design aspect of cutouts under tensile and flexural loading. Detailed analysis of strength, modulus, and variance in failure mechanism has been done to assess the relationship between material strength and design under two different loading conditions. Longitudinal and cross ply stacking sequences are considered. Tensile loading is found to be more detrimental than flexural loading for composite laminate with hole. SEM and optical micrographs have been analyzed to perceive the failure mechanisms of laminates under two different loading conditions. Mode I dominated delamination and mode II dominated delamination are found to be prevalent in OHT (open hole tensile) and OHF (open hole flexural) failure, respectively.